Overview of spatio-temporal distribution inferred by multi-locus sequence typing of Taylorella equigenitalis isolated worldwide from 1977 to 2018 in equidae - Duquesne, Fabien; Merlin, Aurélie; Pérez-Cobo, Iratxe; Sedlák, Kamil; Melzer, Falk; Overesch, Gudrun; Fretin, David; Iwaniak, Wojciech; Breuil, Marie-France; Wernery, Ulrich; Hicks, Jessica; Agüero-García, Montserrat; et al. (Veterinary microbiology, 2020)
The accurate identification of Taylorella equigenitalis strains is essential to improve worldwide prevention and control strategies for contagious equine metritis (CEM). This study compared 367 worldwide equine strains using multilocus sequence typing according to the geographical origin, isolation year and equine breed. The strains were divided into 49 sequence types (STs), including 10 described for the first time. Three major and three minor clonal complexes (CCs), and 11 singletons, were identified. The genetic heterogeneity was low (0.13 STs/strain) despite the wide diversity of geographical origins (n = 16), isolation years (1977-2018) and equine breeds (n = 18). It was highest outside Europe and in the 1977-1997 period; current major STs and CCs already existed before 1998. Previous data associated the major CC1 with the first CEM outbreaks in 1977-1978 in the United Kingdom, Australia and the United States, and revealed its circulation in France. Our study confirms its circulation in France over a longer period of time (1992-2018) and its distribution in Spain and Germany but not throughout Europe. In addition to CC1, relationships between non-European and European countries were observed only through ST4, ST17 and ST30. Within Europe, several STs emerged with cross-border circulation, in particular ST16 and ST46 from the major complexes CC2 and CC8. These results constitute a baseline for monitoring the spread of CEM outbreaks. A retrospective analysis of a higher number of strains isolated worldwide between 1977 and the early 2000s would be helpful to obtain an exhaustive picture of the original CEM situation.
Keywords: Gram-Negative Bacterial Infections; Spojené státy americké; nemoci koní; Phylogeny; Multilocus Sequence Typing; Contagious equine metritis; Evropa; Horses; Disease Outbreaks; časoprostorová analýza; Australia; koně; Europe; zvířata; United States; Taylorellaequigenitalis; Infectious equine disease; Retrospective Studies; Spatio-Temporal Analysis; fylogeneze; multilokusová sekvenční typizace; Bacterial Typing Techniques; Taylorella equigenitalis; Horse Diseases; retrospektivní studie; gramnegativní bakteriální infekce; Animals; MLST; epidemický výskyt choroby; Austrálie; techniky typizace bakterií